ARP3 Controls the Podocyte Architecture at the Kidney Filtration Barrier - Schell, Christoph; Sabass, Benedikt; Helmstaedter, Martin; Geist, Felix; Abed, Ahmed; Yasuda-Yamahara, Mako; Sigle, August; Maier, Jasmin I; Grahammer, Florian; Siegerist, Florian; Artelt, Nadine; Endlich, Nicole; et al. (Developmental cell, 2018)
Podocytes, highly specialized epithelial cells, build the outer part of the kidney filtration barrier and withstand high mechanical forces through a complex network of cellular protrusions. Here, we show that Arp2/3-dependent actin polymerization controls actomyosin contractility and focal adhesion maturation of podocyte protrusions and thereby regulates formation, maintenance, and capacity to adapt to mechanical requirements of the filtration barrier. We find that N-WASP-Arp2/3 define the development of complex arborized podocyte protrusions in vitro and in vivo. Loss of dendritic actin networks results in a pronounced activation of the actomyosin cytoskeleton and the generation of over-maturated but less efficient adhesion, leading to detachment of podocytes. Our data provide a model to explain podocyte protrusion morphology and their mechanical stability based on a tripartite relationship between actin polymerization, contractility, and adhesion.